Contrasting Nordic education policymakers’ reflections on the future across time and space - Hansen, Petteri (Scandinavian Journal of Educational Research, 2023)
In this article, we examine how policymakers from three Nordic countries, Finland, Iceland and Sweden, reflect on the future at 2 different points in time: just before the first PISA study (1998–1999) and more than 15 years later (2015–2017). The empirical data consist of interviews (N = 37) with national policymakers, collected in two comparative Nordic education policy research projects. As a result of this study, we identified three common themes according to which Nordic policymakers discussed the future: (a) school, work, and social equality in a changing society; (b) policies and practices of education governance; and (c) the future of the teaching profession and teacher education. Whereas these themes constitute a shared semantic basis for envisioning the future of Nordic education, contrasting policymakers’ future reflections across time and space also reveals differences, contradictions and changes in ways of thinking about the future. Peer reviewed